Hubungan antara Skemata dan Penguasaan Kosakata dengan Kemampuan Membaca Pemahaman - Nur Jana (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The study aimed to investigate and analyze empirically; (1) the correlation between schemata and students’ achievement on reading; (2) the correlation between vocabulary mastery and students’ achievement on reading; and (3) the correlation between schemata and vocabulary mastery on together with students’ achievement on reading comprehension at English department faculty of teacher training and education of Lakidende University. It used survey method with the correlational approach. The populations were 165 persons and the totals of samples were 70 persons. Objective tests on multiple choices (dichotomously scored item) for all variables were used to collect the data. The results were as follows; (1) there was a significant correlation between schemata and students’ achievement on reading with the regression coefficient (rxy1) was 0.830 and determination coefficient (R Square) was 0.689; (2) there was a significant correlation between vocabulary mastery and students’ achievement on reading with the regression coefficient (rxy1) was 0.954 and determination coefficient (R Square) was 0.910; and (3) there was a significant correlation between schemata and vocabulary mastery in together with students’ achievement on reading comprehension with the regression coefficient (rxy1.2) was 0.960 and determination coefficient (R Square) was 0.921. In conclusion, there weas a significant correlation between schemata and vocabulary mastery in together with students’ achievement on reading comprehension at English department faculty of teacher training and education of Lakidende University.